Bahasa Ambon dan Bahasa Indonesia: Analisis Fonologi - Theresia Meturan; Laraswati Laraswati; Lusi Nur Triani (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
In the context of this research, we apply in-depth qualitative research methods to investigate and analyze the differences and similarities between Ambonese and Indonesian. This approach involves a series of in-depth interviews with native speakers of both languages, allowing us to reconcile complex linguistic aspects and explore the social and cultural contexts that shape language differences in two different environments. Content analysis is also used to explore cultural nuances and linguistic aspects that may not be immediately apparent. By focusing on the relationship between language, identity, and culture, this research aims to provide a deeper understanding of how linguistic differences reflect and influence people's identities. In addition, we seek to explain the practical impact of these language differences in various everyday communication contexts. The results of this research not only have the potential to provide new insights into the structure and use of Ambonese and Indonesian, but can also contribute to a broader understanding of language complexity in multicultural contexts. Therefore, this article not only contributes to the linguistic literature, but also simplifies the practical and cultural implications of language differences in societies that use these two languages ​​in daily interactions.